2011
DOI: 10.4049/jimmunol.1003309
|View full text |Cite
|
Sign up to set email alerts
|

Large TCR Diversity of Virus-Specific CD8 T Cells Provides the Mechanistic Basis for Massive TCR Renewal after Antigen Exposure

Abstract: Ex vivo analysis of virus-specific CD8 T cell populations by anchored PCR has shown that the CD8 TCR repertoire was less oligoclonal (seven to nine clonotypes per individual epitope) than previously thought. In the current study, TCR diversity was investigated by assessing both the overall TCR β-chain variable regions usage as well as the CDR3 regions in ex vivo-isolated CMV- and EBV-specific CD8 T cells from 27 healthy donors. The average number of clonotypes specific to most single viral epitopes comprised b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 55 publications
2
46
1
4
Order By: Relevance
“…Similarly, in this study, we observed a highly focused narrowing of the cross-reactive NLV-specific TCR repertoire before CMV reactivation, which then reduced in immunodominance long after cessation of viral infection. Therefore, our observation supports previous reports (39,47) that antigenic pressure offers to shape the T cell repertoire.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, in this study, we observed a highly focused narrowing of the cross-reactive NLV-specific TCR repertoire before CMV reactivation, which then reduced in immunodominance long after cessation of viral infection. Therefore, our observation supports previous reports (39,47) that antigenic pressure offers to shape the T cell repertoire.…”
Section: Resultssupporting
confidence: 81%
“…To the best of our knowledge, this particular TCRab paired clonotype has not been previously described in the literature, which may be explained by either: 1) limited TCRab paired data available, 2) limited coverage in our population, or 3) private or less public specificity of this clonotype in our population. Based on our and others' data (42), TCRb chains comprising TRBV12-4TRBJ1-2 genes were more frequently observed for conventional NLV-specific CD8 + T cells, whereas TRBV12-4TRBJ1-1 TCRb chains, being a key feature of our cross-reactive OTN5 clonotype, have been previously reported at very low frequencies (38,40,47,49). Nevertheless, this is the first study, to our knowledge, to demonstrate a TRBV12-4TRBJ1-1 TCRb chain pairing with TRAV3TRAJ31 in NLV-specific CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Pol-LI9-specific CD8 T cell populations maintained clonotypic diversity over time after high-dose vaccination, possibly reflecting lower overall Ag avidities and more uniform interclonotypic profiles. Thus, a low-dose vaccination strategy enables broader clonotypic persistence, at least for epitope-specific CD8 T cell populations with diverse available repertoires, thereby seeding a more expansive long-term memory pool (70).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent tetrameric pMHC I complexes of AMQMLKETI/H-2K d (Gag-AI9 [65][66][67][68][69][70][71][72][73] ) and LVGPTPVNI/H-2D d (Pol-LI9 [76][77][78][79][80][81][82][83][84] ) were either provided by the National Institutes of Health Tetramer Core Facility or produced inhouse as described previously (43). Cells were pelleted and resuspended in 200 ml complete RPMI medium and then stained with tetramer (1 mg/test with respect to the pMHC I monomeric component) for 20 min at 37˚C.…”
Section: Tetramer Staining and Flow Cytometric Sortingmentioning
confidence: 99%
“…However, this effect of selection is less apparent in the context of non-persistent antigens (16,34). Studies of EBV and CMV infection have demonstrated that TCR bias can result from the prior selection of T cells with high-affinity TCRs (38,40); virus-specific memory CD8 + T cells have been detected in vitro (41). EBV is a persistent entity that has infected >90% of the population; in this context, biased TCR usage is mainly directed against several EBV antigens (42), and most restricted TCR family members exhibit sequence conservation according to specific antigen epitopes.…”
Section: Tcr Bias In Diseasementioning
confidence: 99%